Relationship of Knowledge, Energy Intake and Family Income with Nutritional Status of the Elderly in Lambara Village, Tawaeli District, Palu City - Moh. Andika Candra; Abdul Hakim Laenggeng; Ayu Lestari (Journal of Public Health and Pharmacy, 2022)
The nutritional problem that can arise after the disaster is the worsening nutritional status of community groups, especially for the elderly group. Energy intake that is not in accordance with the needs of the elderly caused by food assistance that is often delayed, unsustainable and limited local food availability can worsen the existing condition. The problem is even more complex with the lack of family income and lack of knowledge in food preparation. The purpose of this study was to determine the relationship between knowledge, energy intake and family income with the nutritional status of the elderly after the disaster in Lambara Village, Tawaeli District, Palu City. This type of research is analytic with a cross sectional approach which aims to determine the relationship between the independent variables (knowledge, energy intake and family income) with the dependent variable of the nutritional status of the elderly being studied at the same time. The population in this study were all advanced residents in Lambara Village totaling 117 people. A sample of 32 respondents was calculated using the Slovin formula using the proportional random sampling technique. The results showed that there was no significant relationship between knowledge and nutritional status of the elderly (H0 accepted, P = 0.273 > 0.05), there was a significant relationship between energy intake and nutritional status of the elderly (H0 rejected, P = 0.007 < 0.05). and there was a significant relationship between family income and the nutritional status of the elderly (H0 rejected, P = 0.009 > 0.05). It is hoped that elderly family members will continue to provide support and attention to the health conditions of the elderly and supervise when serving food that is in accordance with the physiological conditions and nutritional needs of the elderly.